Relación del rendimiento productivo con el nivel de lesión intestinal y recuento de ooquistes de Eimeria sp utilizando como tratamiento alternativo extracto de Petivera alliaceae y Lippia alba en pollos de engorde - Flores Herrera, Jhonny Gersson (2018)
Coccidiosis is a parasitic disease caused by a unicellular protozoan, of the genus Eimeria, whose quality is a product of the economic consequence for the poultry industry, due to the intestinal damage that it cause. It is also looking for alternative methods to control this disease, such as the use of plants. The present study aims to evaluate the effect of 2 plant extracts (Petiviera alliaceae and Lippia alba), measuring the productive performance, the degree of the intestinal lesions and elimination of oocysts in broilers experimentally challenged with strains of Eimeria sp. and bred up to 28 days of age. A total of 125 male 1 day-old chicks BB from the Cobb 500 line, from the same batch of breeders, were used, which were divided into 5 group (3 controls and 2 groups treated with the extracts of natural plants), each one of these groups consisted of 25 chicks. The stool samples were collected in sterile bottles on days 14, 17, 21, 24 and 28 for the estimation of oocysts per gram of feces, by the qualitative method of Willis – Molloy and the modified quantitative method of McMaster. No differences were found (P < 0.05) in the productive indexes, but it was found that the treatments attenuated the intestinal lesions and decreased the number of oocysts per gram of feces. It can be concluded that both treatments can control coccidiosis and it is recommended to continue with the investigations, using different doses to observe their effects.